Students' Perception and Readiness Level Toward Interprofessional Education (IPE) Before and After Program Implementation - Muhammad Rizal Novianto; Abdul Malik Setiawan; Zidnal Mafaz (Journal of Islamic Medicine, 2022)
Background: The changing health system and the large number of patients presenting with chronic diseases require multi-disciplinary care. For this reason, Interprofessional Education (IPE) needs to be conducted to train teamwork between these health workers.  Furthermore, to develop the IPE program at the faculty, it is necessary to have a good evaluation.  In Kirkpatrick's evaluation model, an assessment of student perceptions and readiness can be carried out to evaluate IPE implementation.  Therefore, the differences in perceptions and readiness at the beginning and after IPE implementation need to be carried out to assess the program.  Objective: The purpose of this study is to find out the overview and comparison of perception and readiness level before and after the implementation of IPE. Methods: This research was a comparative quantitative study with a pre-experimental one-group pretest-posttest design with data collection using questionnaires. The type of data used in this study was primary data using Student Perception of Physician and Pharmacist Interprofessional Clinical Education (SPICE) and the Readiness for Interprofessional Learning Scale (RIPLS) questionnaires. 81 final semester academic students of the pharmacy and medical study program were collected to measure their level of perception and readiness for IPE before and after the implementation of IPE. The data were analyzed using the SPSS computer program.  Result: Perception result before IPE was 4.29 (scale 1-5) and 4.49 after IPE.  As for the results of readiness, 4.15 before IPE and 4.29 after IPE.  There was a significant increase in students' perceptions and readiness after the implementation of IPE (P0.005). Conclusion: Most students have a good perception and readiness for IPE and there is a significant increase after IPE. Keywords: Interprofessional Relations, Professional Education, Questionnaire Design, Interdisciplinary